2013
DOI: 10.1155/2013/183041
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-Induced Effects on Lipids and Inflammation

Abstract: Chronic pain has to be considered in all respects a debilitating disease and 10–20% of the world's adult population is affected by this disease. In the most general terms, pain is symptomatic of some form of dysfunction and (often) the resulting inflammatory processes in the body. In the study of pain, great attention has been paid to the possible involvement of gonadal hormones, especially in recent years. In particular, testosterone, the main androgen, is thought to play a beneficial, protective role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 86 publications
1
44
0
3
Order By: Relevance
“…Sustained increased production of high levels of proinflammatory mediators in the local microenvironment triggers a cascade of events that, in some individuals, results in extensive and irreversible degradation of both mineralized and non‐mineralized connective tissues of the periodontium . The biological activity of various cytokines and inflammatory mediators in the periodontal microenvironment may be directly related to the extent and severity of periodontal tissue destruction; however, the very production of these mediators can be influenced by environmental, genetic and systemic factors, including changes in the serum levels of sexual hormones, which are potent modulators of inflammation . In fact, our research group has reported on the influence of testosterone on bone tissue in association with the regulation of local production of cytokines …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Sustained increased production of high levels of proinflammatory mediators in the local microenvironment triggers a cascade of events that, in some individuals, results in extensive and irreversible degradation of both mineralized and non‐mineralized connective tissues of the periodontium . The biological activity of various cytokines and inflammatory mediators in the periodontal microenvironment may be directly related to the extent and severity of periodontal tissue destruction; however, the very production of these mediators can be influenced by environmental, genetic and systemic factors, including changes in the serum levels of sexual hormones, which are potent modulators of inflammation . In fact, our research group has reported on the influence of testosterone on bone tissue in association with the regulation of local production of cytokines …”
Section: Discussionmentioning
confidence: 83%
“…These mediators indirectly mediate degradation of non‐mineralized and mineralized tissue degradation by inducing the production of matrix metalloproteases and osteoclast‐inducing and activating receptor activator of nuclear factor kappa‐B ligand (RANKL), resulting in the resorption of the alveolar bone . In this context, steroid hormones, including sex hormones, are potent modulators of inflammation and bone turnover . Testosterone has an immunossupressive effect, as indicated by the decrease of macrophage and lymphocyte T helper (CD4+ T) cell infiltration in experimental autoimmune orchitis in rats, and these effects were associated with reduced production of proinflammatory mediators monocyte chemoattractant protein‐1 (MCP‐1), TNF, IL‐6 and IFN‐ in the draining lymph nodes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is characterized by intestinal inflammation which leads to progressive bowel damage, increasing disability and a loss of quality of life, and the treatment is cumbersome. In recent years, a significant role of testosterone as an immune modulator [3] in a large number of disease entities such as cardiovascular disease [41], rheumatoid arthritis [42] or inflammatory processes of the central nervous system [43] has become apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes play a significant role in the etiology of cardiovascular disease, and testosterone shows anti-inflammatory effects [1]. Several studies have documented that low testosterone levels are associated with an increase in inflammatory factors and that administration reduces their levels (for review [2,3]). There is evidence showing an immunomodulatory and protective effect of testosterone in a model of chronic testicular inflammation and testosterone as a new factor in the differentiation of regulatory T cells [4].…”
Section: Introductionmentioning
confidence: 99%